Characterization of myocardial sodium-glucose cotransporter 1 expression in humans with heart failure and reduced ejection fraction. (25th November 2020) - Sayour, A.A; Olah, A; Ruppert, M; Hartyanszky, I; Polos, M; Barta, B.A; Benke, K; Merkely, B; Radovits, T
Abstract: Introduction: In diabetic patients, multiple cardiovascular outcome trials consistently showed the robust cardioprotective effects of the novel antidiabetic agents, sodium glucose cotransporter 2 (SGLT2) inhibitors. However, the DAPA-HF study using the SGLT2 inhibitor dapagliflozin have extended these observations onto non-diabetic patients with heart failure (HF), urging previous hypotheses regarding the cardioprotective effects of SGLT2 inhibitors to be revised. This is further complicated by the fact that SGLT2 is not expressed in the human myocardium neither under normal nor diseased states. Hence, it has been postulated that SGLT2 inhibitors might exert direct cardioprotection via non-specific inhibition of SGLT1, which is in turn highly expressed in the myocardium. Purpose: Because literature data is scarce regarding the expression profile of myocardial SGLT1, we aimed to characterize left ventricular SGLT1 expression in humans with end-stage HF accordingly to HF aetiology and to investigate whether cardiac resynchronization therapy (CRT) affects SGLT1 expression. Methods: From patients undergoing mitral valve replacement with otherwise no myocardial disease and preserved LV function, we collected control papillary muscles (Control, n=9). From patients with end-stage HF undergoing heart transplantation (n=72), we obtained LV anterior wall samples according to the following HF aetiology groups: hypertrophic cardiomyopathy (HCM, n=7); idiopathic dilated cardiomyopathy (DCM, n=12); ischaemic heart disease (IHD, n=14), IHD with type 2 diabetes mellitus (IHD+T2DM, n=11); and patients with CRT (CRT-DCM, n=9; CRT-IHD, n=9; CRT-IHD+T2DM, n=10). We measured LV SGLT1 expression on the gene and protein expression levels using qRT-PCR and western blotting, respectively. Echocardiography-derived LV end-diastolic diameter (LVEDD) and LV ejection fraction (LVEF) were registered prior to surgery. Results: Compared to controls, LV SGLT1 mRNA and protein expressions were significantly upregulated in patients with DCM, IHD and IHD+T2DM (all P<0.05), but not in HCM. In these patient groups, LV SGLT1 mRNA expression showed a significant positive correlation with LVEDD (r=0.493; P<0.001) and significant negative correlation with LVEF (r=−0.477; P<0.001). On the protein expression level, CRT was associated with significant reduction in LV SGLT1 only in patients with DCM and IHD, but not in IHD+T2DM. Conclusions: Myocardial SGLT1 is upregulated in patients with HF (except HCM), and correlated strongly with parameters (LVEDD, LVEF) related to adverse LV remodelling. CRT was associated with reduced SGLT1 expression in DCM and IHD patients, but not in those with IHD+T2DM. Our results suggest that SGLT1 is upregulated in HF and might be implicated in adverse myocardial remodelling. Accordingly, whether SGLT2 inhibitors exert direct cardioprotection in HFrEF via non-specific inhibition of SGLT1 needs to be further elucidated. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Fund of Hungary, Higher Education Institutional Excellence Programme of the Ministry of Human Capacities of Hungary